Fashion marketing : influencing consumer choice and loyalty with fashion products - Le Bon, Caroline (New York, New York (222 East 46th Street, New York, NY 10017) : Business Expert Press, 2015)
Fashion is everywhere! It transcends domains and applies to almost any kind of product (e.g., apparel, cars, digital devices, food, literature, travel, music, house decoration, and personal wellness). Fashion greatly influences public interest, media coverage, and product success. In this global industry, many actors interact, including designers, suppliers, and retailers, who collaborate to sell apparel and accessories. In addition, the global fashion industry is among the most important in terms of investments, trade, and employment, despite its dependence on unpredictable demand. Thus, fashion companies face a dilemma: On the one hand, they repeatedly create ephemeral products that must seduce customers each time; whereas on the other hand, the products need to provide continual profits. A key challenge for fashion managers is to design and launch new fashion products that will achieve success with customers during their very short life spans, in which setting they also affect consumers' personal seductiveness, desire, and appearance. For example, will the long skirt have the same success than the skinny jean, or will the high heel prevail over the flats? A fashion dress is more than just a dress--it can change people's appearance and reveal consumers' identity. Consequently, fashion managers are responsible for not just their product lines but also the self-images they help customers convey. This book focuses on the fashion apparel and accessories industry in an attempt to help managers answer the following questions: Why and how do fashion products appeal to consumers, despite their constantly varying attributes? What specific elements and benefits of fashion influence consumers, and how can companies exploit them and gain from these? Which marketing strategies and tactics should companies use to increase fashion products' success while communicating and managing customers' image? How can companies maintain customers' loyalty and generate higher profits with fashion products? By undertaking deep analyses of manufacturers and retailers' best practices, interviewing customers and companies, and reviewing recent academic research on fashion marketing, this book answers such questions and thus helps managers leverage the value that fashion adds to products while creating loyal customers in truly competitive fashion markets.
Preface -- Acknowledgments -- Introduction -- 1. Fashion as the empire of seduction -- 2. Fashion as a world of influences -- 3. Fashion and product variety -- 4. Overseeing cost and price in fashion marketing -- 5. Fashion as a means of communication -- 6. Managing channels of distribution and enhancing fashion's impact -- 7. Leveraging fashion equity, the absolute benefit -- 8. Handling managers' challenges for successful fashion products -- Conclusion -- About the author -- Notes -- References -- Index.
Part of: 2014 digital library.
Includes bibliographical references (pages 115-119) and index.
Title from PDF title page (viewed on October 13, 2014).
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Fashion merchandising; customer loyalty; fashion; fashion equity; fashion marketing; social influence; symbolic influence; Electronic books